Influence of the Pension 65 Program on the well-being of users in the Province of Chupaca 2020 – 2021 - Rivera Medrano, José Luis (2023)
The objective of the research was to determine how the Pension 65 Program influences the quality of life of users in the province of Chupaca 2020 - 2021. The research design was non-experimental because variables were not manipulated. Being a descriptive study, with a cross section, it was carried out in a certain time (2020-2021). The population we studied was made up of 1638 users and a sample of 287 users by exclusion and inclusion criteria. We used the survey as a technique, then two instruments, two questionnaires: the first with a dichotomous answer for Program P65, the second questionnaire with a scale of several polytomous answers for quality of life. We validate our instrument by Expert judgment, to analyze our relationship of variables we apply Spearman's Rho coefficient = .050. In our results we conclude that the Pension 65 variable influences the well-being of life through economic security in users belonging to the province of Chupaca - Junín 2020 - 2021, the degree of significance is presented, p <0.05 and Spearman's Rho coefficient = .660 with a variance of the P65 Program and well-being of life with an influence of 0.01 %.